ANALISIS DAMPAK PENAMPILAN DIRI TERHADAP SELF CONFIDENCE MAHASISWA UNIVERSITAS TEKNOLOGI YOGYAKARTA - Lenny Anca Pramesty; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Students need to pay attention to good self-appearance because this can give a positive impression and other people can describe their good personality. In addition, paying attention to self-appearance can increase the level of self-confidence of students because they will feel confident, brave about what is being done and can think more creatively and will even feel more confident when speaking in public because the student already looks as desired. This research uses qualitative methods with interview instruments and documentation studies. The impact of self-appearance on student self-confidence states that self-appearance is very influential because with a maximum self-appearance according to himself and comfortable with this appearance can foster more confidence. Self-appearance can reflect one's personality because by paying attention to self-appearance others will judge ourselves more positively. Someone who pays attention to their appearance is usually very concerned about neatness, politeness, cleanliness and suitability of clothing colors. Paying attention to personal appearance can increase learning motivation and student learning outcomes